Opportunistic networks: mobility models, protocols, security, and privacy - Ahmad, Khaleel (Taylor and Francis, 2019)
Opportunistic networks allow mobile users to share information without any network infrastructure.This book is suitable for both undergraduates and postgraduates as it discusses various aspects of opportunistic networking including, foundations of ad hoc network; taxonomy of mobility models, etc.